Analisis Putusan MK No 85/PUU-XX/2022 Tentang Pembentukan Badan Peradilan Khusus Pemilu Ditinjau Dari Teori Kedaulatan Hukum - Yusuf Apriyanto Bantu; Erman I Rahim; Abdul Hamid Tome (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
This article conducts a normative analysis of the Constitutional Court's Decision No. 85/PUU-XX/2022 concerning the establishment of a special electoral court within the framework of legal sovereignty theory. The objective is to scrutinize the decision's compatibility with the principles of legal sovereignty, emphasizing the universal application of law. The normative method is employed, focusing on legal documents, statutes, and constitutional provisions. The study reveals that the decision's implications raise concerns regarding the universal enforcement of law in addressing complex electoral disputes. The absence of a special electoral court challenges the effective resolution of election-related issues. This analysis contributes to the ongoing discourse on the role of legal sovereignty in shaping the electoral dispute resolution system